2012
DOI: 10.1186/1472-6882-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of sesquiterpene lactones isolated from traditional medicinal plant, Costus speciosus (Koen ex.Retz.) Sm

Abstract: BackgroundCostus speciosus (Koen ex.Retz.) Sm (Costaceae) is an Indian ornamental plant which has long been used medicinally in traditional systems of medicine. The plant has been found to possess diverse pharmacological activities. Rhizomes are used to treat pneumonia, rheumatism, dropsy, urinary diseases, jaundice, skin diseases and leaves are usedto treat mental disorders.MethodAntibacterial and antifungal activities were tested using Disc diffusion method and Minimum Inhibitory Concentration (MIC). Column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 31 publications
2
47
0
5
Order By: Relevance
“…S1D to F). Furthermore, oxygenous sesquiterpenoids that have been oxidized from oxygen-free sesquiterpenoids have stronger antimicrobial activity (46). These processes restrict the overgrowth of endophytes in planta (47) and are essential strategies used by host plants to modulate the growth of endophytes in vivo and to maintain a mutualistic relationship with endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…S1D to F). Furthermore, oxygenous sesquiterpenoids that have been oxidized from oxygen-free sesquiterpenoids have stronger antimicrobial activity (46). These processes restrict the overgrowth of endophytes in planta (47) and are essential strategies used by host plants to modulate the growth of endophytes in vivo and to maintain a mutualistic relationship with endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…59, No.1A, pp: 38-43 04 existence of phenolic and alkaloid compounds. [2] Quercetin, Rutin, Luteolin, Kaempherol and Coumarin showed strong antibacterial activity in many studies [6]. …”
Section: Antibacterial Activity Testmentioning
confidence: 99%
“…Also herbal products are safer, less expensive and infrequently have side effects in comparison with synthetic drugs [1]. Among various herbals valued, C. speciosus is an erect herbaceous pharmacologically important one [2]. Costus speciosus is pharmaceutical and decorative plant cultivated in India crepe ginger belongs to family Costaceae (Zingiberaceae) [3].…”
mentioning
confidence: 99%
“…Saussurea costus is considered to be one of the antioxidant-rich medicinal plants. Many authors have reported that the roots of this plant possess various biological activities, including cortisol lowering effect [38], anti-infammatory [39,40], anticancer [41,42], antiviral [23], antimicrobial [43,44], antifungal [15], antioxidant [45,46], antidiabetic [47], antiulcer [20] and hepatoprotective effects [38]. Liv-52 is widely used in treatment of liver diseases of varying origins.…”
Section: Discussionmentioning
confidence: 99%